Evaluation of Animation-Based Reading Learning System during the Covid-19 Pandemic Using the Usability Scale System - Rama Haryamadha; Ilyas Nuryasin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In recent years, the world is facing a big problem that started with the emergence of an outbreak of a disease caused by the corona virus or familiarly called Covid-19. Almost all aspects of life are affected and undergo significant changes. So because Covid-19 pandemic teaching and learning activities apply distance learning from home with an online model or online learning. Distance learning is a planned teaching and learning activity outside the classroom environment and there is no face-to-face interaction between students and teachers this learning emphasizes independent learning. This policy requires all educational institutions to be active and innovative in designing their learning activities. With innovations in distance learning during the Covid-19 pandemic, students will feel enthusiastic and lose boredom during activities, learning is more varied and students are not bored to increase the interactiveness of learning, it uses an animation-based reading system to see what features are lacking, so it is necessary to evaluate so that there will be improvements in the future. System Usability Scale is one of the evaluation methods used to see the usability of a software product. Usability evaluation was carried out to 10 student user respondents across generations. Based on the results of the Usability evaluation, the animation-based learning to read platform has a score of 88 and is considered to have met the Usability element.